2009
DOI: 10.5194/gh-64-134-2009
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of tourism on geomorphological processes in the Bucegi Mountains in Romania

Abstract: Abstract. The Bucegi Mountains are situated in the Curvature Carpathians close to the metropolitan area of Bucharest. Tourism has been promoted on the Bucegi Plateau since the 1930s with the establishment then of several hotels and chalets. During the communist period after World War II, the area targeted mass tourism with the creation of a large network of hiking paths. Increased heating needs led to the almost complete removal of dwarf pine cover. The current situation is characterised by intense vegetation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…Planning and designing solutions that integrate people's needs, WB, and the ecosystem functioning are more sustainable. Knowing ES supply and demand gaps are important for providing the WB of citizens [11,12]. The benefits provided depend not only on the ability of an ecosystem to provide services, but also on the demand for those services, which depends on many different factors, including cultural factors and the perceived value of the service [13].…”
Section: Introductionmentioning
confidence: 99%
“…Planning and designing solutions that integrate people's needs, WB, and the ecosystem functioning are more sustainable. Knowing ES supply and demand gaps are important for providing the WB of citizens [11,12]. The benefits provided depend not only on the ability of an ecosystem to provide services, but also on the demand for those services, which depends on many different factors, including cultural factors and the perceived value of the service [13].…”
Section: Introductionmentioning
confidence: 99%
“…Given the lack of data on the distribution of tourists in each given elevation zone, it is difficult to know which factor is more important -volume of tourist traffic or local environmental conditions. The magnitude of relief change in the study area was found to be smaller than that in the les Monts Dore Massif in France and Bucegi Mountains in Romania (Krzemień 1997(Krzemień , 2010Mihai et al 2009). The presence of deep gullies was noted in the aforementioned areas.…”
Section: Footpath Identifiermentioning
confidence: 67%
“…The very unique characteristics of mountain areas and local determinants, especially bedrock resistance and magnitude of human impact, determine the magnitude of relief change in mountain areas (Leung and Marion 1996;Mihai et al 2009;Monz et al 2010a;Tomczyk 2011;Lepeška 2016;Apollo and Andreychouk 2020; Table 4 Location of analyzed tourist footpath sections and rate of growth of their zones of degradation in the years 1977-2009-2019 (location of footpath sections see Fig. 8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional factor that increases the activity of erosive processes in high mountains is hiking [ 10 , 11 , 12 ]. The anthropogenic degradation on hiking trails on slopes is currently the subject of research, both in Poland [ 13 , 14 ] and worldwide [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%